Sex Differences are Reflected in Microstructural White Matter Alterations of Musical Sophistication: A Diffusion MRI Study - Mehrabinejad, Mohammad-Mehdi; Rafei, Parnian; Sanjari Moghaddam, Hossein; Sinaeifar, Zeinab; Aarabi, Mohammad Hadi (Frontiers in Neuroscience, 2021)
Background: The human-specified ability to engage with different kinds of music in sophisticated ways is named “Musical Sophistication”. Herein, we investigated specific white matter (WM) tracts that are associated with musical sophistication and musicality in both genders, separately, using the Diffusion MRI connectometry approach. Methods: 123 healthy participants (70 (56.9%) were male, mean age=36.80±18.86 year), who were evaluated for musical sophistication using Goldsmiths Musical Sophistication Index (Gold-MSI) self-assessment instrument from the LEMON database, were recruited in this study. The WM correlates of two Gold-MSI subscales (active engagement and music training) were analyzed. Images were prepared and analyzed with diffusion connectometry to construct the local connectome. Multiple regression models were then fitted to address the correlation of local connectomes with Gold-MSI components with the covariates of age and handedness. Results: a significant positive correlation between WM integrity in the corpus callosum (CC), right corticospinal tract (CST), cingulum, middle cerebellar peduncle (MCP), bilateral parieto-pontine tract, right cerebellum, and left arcuate fasciculus (AF) and both active engagement (false discovery rate (FDR)=0.008) and music training (FDR=0.057) was detected in males. However, WM integrity in the body of CC, MCP, and cerebellum in females showed an inverse association with active engagement (FDR=0.046) and music training (FDR=0.032). Conclusion: WM microstructures with functional connection with motor and somatosensory areas (CST, cortico-pontine tracts, CC, cerebellum, cingulum, and MCP) and language processing area (AF) have a significant correlation with music engagement and training.